Strengthening primary eye care in South Africa: An assessment of services and prospective evaluation of a health systems support package. - Rivka R Lilian; Jean Railton; Erik Schaftenaar; Moyahabo Mabitsi; Cornelis J Grobbelaar; N Sellina Khosa; Babra H Maluleke; Helen E Struthers; James A McIntyre; Remco P H Peters (PLoS ONE, 2018)
Visual impairment is a significant public health concern, particularly in low- and middle-income countries where eye care is predominantly provided at the primary healthcare (PHC) level, known as primary eye care. This study aimed to perform an evaluation of primary eye care services in three districts of South Africa and to assess whether an ophthalmic health system strengthening (HSS) package could improve these services. Baseline surveys were conducted in Cape Winelands District, Johannesburg Health District and Mopani District at 14, 25 and 36 PHC facilities, respectively. Thereafter, the HSS package, comprising group training, individual mentoring, stakeholder engagement and resource provision, was implemented in 20 intervention sites in Mopani District, with the remaining 16 Mopani facilities serving as control sites. At baseline, less than half the facilities in Johannesburg and Mopani had dedicated eye care personnel or sufficient space to measure visual acuity. Although visual acuity charts were available in most facilities, <50% assessed patients at the correct distance. Median score for availability of nine essential drugs was <70%. Referral criteria knowledge was highest in Cape Winelands and Johannesburg, with poor clinical knowledge across all districts. Several HSS interventions produced successful outcomes: compared to control sites there was a significant increase in the proportion of intervention sites with eye care personnel and resources such as visual acuity charts (p = 0.02 and <0.01, respectively). However, engaging with district pharmacists did not improve availability of essential drugs (p = 0.47). Referral criteria knowledge improved significantly in intervention sites (p<0.01) but there was no improvement in clinical knowledge (p = 0.76). Primary eye care in South Africa faces multiple challenges with regard to organisation of care, resource availability and clinical competence. The HSS package successfully improved some aspects of this care, but further development is warranted together with debate regarding the positioning of eye services at PHC level.